Psychological determinants of pre-hypertension among first year undergraduate students in a public university in Malaysia - A. D., Balami; Md Said, Salmiah; Mohd Zulkefli, Nor Afiah (Malaysian Public Health Physicians’ Association, 2014)
Pre-hypertension increased the risk of morbidity and mortality from non-communicable diseases. Whereas, psychological factors such as depression, anxiety and stress have been associated with increased in blood pressure. However, previous studies more focuses on psychological determinants of hypertension than prehypertension. Thus, this study aims to determine the association between these psychological factors with pre-hypertension. A cross-sectional study was conducted in 2012 among first year students of a public Malaysian university. A random cluster sampling was used to select 5 out of 15 faculties and a total of 495 students participated in this study. The Malay version of DASS-21 was used to elicit their levels of depression, anxiety and stress. Blood pressures were measured twice using sphygmomanometer and the averages were taken. Data analyses used chi-square test and binary multiple logistic regression. The prevalence of pre-hypertension was 30.1%. The percentage of severe and extremely severe depression was 3.8% and 1.2%; both severe and extremely severe anxiety was 16.4%; and severe and extremely severe stress was 4.2% and 0.2% respectively. Severe/extremely severe depression had more than 3 times higher in getting pre-hypertension than no depression. In conclusions, almost one third of respondents had pre-hypertension and only severe/extremely depression was associated with pre-hypertension.